Sistem Pengaturan Suhu Dan Kelembaban Kandang Ayam Menggunakan Arduino Dan Website - Bagus Dwi Maulana; Djoni Haryadi Setiabudi; Resmana Lim (Jurnal Infra, 2020)
Chicken raising is one activity that is still widely carried out by people who want to do business in the field of chicken farming, especially in Indonesia because the average human consumes chicken meat almost every day. Broiler breeders in Indonesia generally use the type of open cages and still use manual methods in the process of raising livestock such as in regulating the temperature of chicken coops. To help and support farmers in the field of maintenance, temperature and humidity regulators are made in the broiler chicken coop automaticallyChicken coops installed system Arduino WeMos D1 R2 and sensors DHT 22 which will show the current temperature and humidity figures and data obtained from the sensor will be sent with WiFi connectivity contained in the microcontroller to the database. This communication will trigger data exchange in real-time between the website and the chicken coop.Based on the results of tests that have been done, the DHT 22 sensor is able to read the situation in the chicken coop by staying in the user's point settings. Users can set point on the website as needed. Websites and devices can be integrated into a WiFi network and store in a database.